2021
DOI: 10.1107/s2052252521001159
|View full text |Cite
|
Sign up to set email alerts
|

Crystallographic models of SARS-CoV-2 3CLpro: in-depth assessment of structure quality and validation

Abstract: The appearance at the end of 2019 of the new SARS-CoV-2 coronavirus led to an unprecedented response by the structural biology community, resulting in the rapid determination of many hundreds of structures of proteins encoded by the virus. As part of an effort to analyze and, if necessary, remediate these structures as deposited in the Protein Data Bank (PDB), this work presents a detailed analysis of 81 crystal structures of the main protease 3CLpro, an important target for the design of drugs against COVID-1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
24
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(35 citation statements)
references
References 59 publications
8
24
0
Order By: Relevance
“…In this regard, neutron scattering experiments [ 20 ] conducted at pH 6.6 and room temperature have shown that HIS41 is protonated and CYS145 is deprotonated on the SARS-CoV-2 3CL pro protein also. This is at variance with the results presented on a previous study by the same authors [ 18 ], in agreement with the consensus base catalysis mechanism [ 22 ] and with the results obtained in Ref. [ 23 ] on the homologous SARS-CoV-1 3CL pro , where the measured pKa of CYS (8.3) and HIS (6.4) are consistent with a general base catalysis Chymotrypsin mechanism and cannot be explained by a thiolate-imidazolium ion pair model.…”
Section: Introductionsupporting
confidence: 89%
See 2 more Smart Citations
“…In this regard, neutron scattering experiments [ 20 ] conducted at pH 6.6 and room temperature have shown that HIS41 is protonated and CYS145 is deprotonated on the SARS-CoV-2 3CL pro protein also. This is at variance with the results presented on a previous study by the same authors [ 18 ], in agreement with the consensus base catalysis mechanism [ 22 ] and with the results obtained in Ref. [ 23 ] on the homologous SARS-CoV-1 3CL pro , where the measured pKa of CYS (8.3) and HIS (6.4) are consistent with a general base catalysis Chymotrypsin mechanism and cannot be explained by a thiolate-imidazolium ion pair model.…”
Section: Introductionsupporting
confidence: 89%
“…The 3CL pro dimer has two symmetric extended clefts for optimal (linear) peptide chain adhesion [ 35 ]. The dimer interface involves the N-terminus of domain I + II and the C-terminus of domain III with no participation of the distal and solvent exposed catalytic site [ 22 , 35 ]. When expressed independently, while domain III has no role in the catalysis [ 33 ], the isolated domain I + II is still capable of cleaving a 14-mer peptidic substrate mimicking the N-terminal autocleavage sites of the SARS 3CL pro , although with a much smaller turnover number with respect to the 3CL pro dimer [ 33 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The divergence of the PDB from the Cambridge Structural Database (CSD) has also led to concerns by the CCDC (Cambridge Crystallographic Data Centre) itself about the quality of ligand structures in the PDB (Liebeschuetz et al, 2012): 'The good, the bad and the twisted: a survey of ligand geometry in protein crystal structures'. This has been reiterated by Jaskolski et al (2021) in a study of nearly 100 coronavirus main protease crystal structures deposited in the PDB, who concluded with a list of problems associated with reliability of the deposited structures, and offered a list of procedural weaknesses of these database depositions.…”
Section: Challenges To Structure Precisionmentioning
confidence: 99%
“…Several collaborative papers were also dedicated to proper validation of atomic models of macromolecules and the identification of 'bad apples' among published results [25][26][27][28][29][30]. Recently, Alex has been instrumental in validating the structures of proteins from the SARS-CoV-2 coronavirus that are rapidly accumulating in the PDB in response to the COVID-19 pandemic [31][32][33][34].…”
mentioning
confidence: 99%